Is Preimplantation Genetic Testing Associated with Increased Risk of Abnormal Placentation After Frozen Embryo Transfer? - Swanson, Kate; Huang, David; Kaing, Amy; Blat, Cinthia; Rosenstein, Melissa G.; Mok-Lin, Evelyn; Gras, Joanne; Sperling, Jeffrey D. (American Journal of Perinatology, 2020)
Objective This study aimed to assess the association of preimplantation genetic testing (PGT) with abnormal placentation among a cohort of pregnancies conceived after frozen embryo transfer (FET).Study Design This is a retrospective cohort study of women who conceived via FET at the University of California, San Francisco from 2012 to 2016 with resultant delivery at the same institution. The primary outcome was abnormal placentation, including placenta accreta, retained placenta, abruption, placenta previa, vasa previa, marginal or velamentous cord insertion, circumvallate placenta, circummarginate placenta, placenta membranacea, bipartite placenta, and placenta succenturiata. Diagnosis was confirmed by reviewing imaging, delivery, and pathology reports. Our secondary outcome was hypertensive disease of pregnancy.Results A total of 311 pregnancies were included in analysis; 158 (50.8%) underwent PGT. Baseline demographic characteristics were similar between groups except for age at conception and infertility diagnosis. Women with PGT were more likely to undergo single embryo transfer (82.3 vs. 64.1%, p < 0.001). There were no statistically significant differences in the rate of the primary outcome (26.6 vs. 27.4%, p = 0.86) or hypertensive disorders of pregnancy (33.5 vs. 33.3%, p = 0.97), which remained true after multivariate analysis was performed.Conclusion Among pregnancies conceived after FET, PGT is not associated with a statistically significant increased risk of abnormal placentation or hypertensive disorders of pregnancy.Key Points
Keywords: abnormal placentation; frozen embryo transfer; in vitro fertilization; preimplantation genetic testing